SALES INFORMATION SYSTEM USING APP FOR SMALL SHOPS - Rakhmawati; Yudhi Prasetya Mada (International Journal of Innovations in Engineering Research and Technology, 2025)
The massive use of technology and digitalization, along with the development of app-based businesses that currently use a lot of information technology. Business efficiency is one of the reasons why many small businesses implement information technology because of the demands of increasingly fierce competition. This plays a central role in the development of small businesses in the current era of development, so small businesses must have the ability to quickly adapt to changes that occur. The purpose of this study is to create a clear and easily accessible sales media for consumers and easy to manage by small business actors. For this reason, an app-based sales information system was designed. This study will describe the activities and products produced at each stage of app design. The design of this information system is only limited to the sales information system and sales transaction database.